Acetylenes and fatty acids from Codonopsis pilosula - Yueping Jiang; Yufeng Liu; Qinglan Guo; Zhibo Jiang; Chengbo Xu; Chenggen Zhu; Yongchun Yang; Sheng Lin; Jiangong Shi (Elsevier, 2015)
Four new acetylenes (1-4) and one new unsaturated ω-hydroxy fatty acid (5), together with 5 known analogues, were isolated from an aqueous extract of Codonopsis pilosula roots. Their structures were determined by spectroscopic and chemical methods. The new acetylenes are categorized as an unusual cyclotetradecatrienynone (1), tetradecenynetriol (2), and rare octenynoic acids (3 and 4), respectively, and 3 and 4 are possibly derived from oxidative metabolic degradation of 1 and/or 2. The absolute configuration of 1 was assigned by comparison of the experimental circular dichroism (CD) spectrum with the calculated electronic circular dichroism (ECD) spectra of stereoisomers based on the quantum-mechanical time-dependent density functional theory, while the configuration of 2 was assigned by using modified Mosher׳s method based on the MPA determination rule of ΔδRS values for diols.